2001
DOI: 10.1073/pnas.121179898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anesthesia on functional activation of cerebral blood flow and metabolism

Abstract: Functional brain mapping based on changes in local cerebral blood flow (lCBF) or glucose utilization (lCMRglc) induced by functional activation is generally carried out in animals under anesthesia, usually ␣-chloralose because of its lesser effects on cardiovascular, respiratory, and reflex functions. Results of studies on the role of nitric oxide (NO) in the mechanism of functional activation of lCBF have differed in unanesthetized and anesthetized animals. NO synthase inhibition markedly attenuates or elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
106
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 42 publications
(52 reference statements)
20
106
1
Order By: Relevance
“…The lCMRglc value determined by the ␤-MICROPROBE for the somatosensory cortex is comparable to the values obtained by using 2-deoxy-D-[ 14 C]glucose autoradiography: 67 Ϯ 2 mol͞100 ml per min under thiopental sodium anesthesia and 118 Ϯ 3 mol͞100 ml per min in the conscious-restrained state (1). The lCMRglc in striatum derived from the ␤-MICROPROBE measurements is similar to that estimated with FDG autoradiography (21) and somewhat higher to that determined by using FDG micro-PET, for which partial volume effects lead to underestimation of lCMRglc as reported by Moore et al (22).…”
Section: Anaesthetized Ratssupporting
confidence: 67%
“…The lCMRglc value determined by the ␤-MICROPROBE for the somatosensory cortex is comparable to the values obtained by using 2-deoxy-D-[ 14 C]glucose autoradiography: 67 Ϯ 2 mol͞100 ml per min under thiopental sodium anesthesia and 118 Ϯ 3 mol͞100 ml per min in the conscious-restrained state (1). The lCMRglc in striatum derived from the ␤-MICROPROBE measurements is similar to that estimated with FDG autoradiography (21) and somewhat higher to that determined by using FDG micro-PET, for which partial volume effects lead to underestimation of lCMRglc as reported by Moore et al (22).…”
Section: Anaesthetized Ratssupporting
confidence: 67%
“…This rate was approximately half that observed in rat brain after 2 h of glucose administration (Choi et al, 1999). It is interesting to note that metabolic rates in the conscious rat brain are typically two to three times faster than those in humans (Gruetter et al, 2001;Nakao et al, 2001). Independent of the precise value of the label turnover rate, the present study clearly demonstrates that metabolism of bulk brain glycogen is very slow.…”
Section: Discussionsupporting
confidence: 50%
“…Our choice of anesthetic dose was based on cerebral metabolism studies. Dudley and colleagues (Dudley et al, 1982) reported that a 60mg/kg single dose of α-chloralose reduces the cerebral glucose utilization rate to 35−47% of that in the awake preparation in the cortex, and Nakao et al (2001) found thata 50mg/kg bolus followed by a 40 mg/kg/h maintenance dose reduced glucose utilization to 36% in the sensory motor cortex. These reductions in cerebral glucose metabolism in the cortex are very similar to the reductions observed with isoflurane at the concentrations used in the present study (Krafft et al, 2000;Ori et al, 1986).…”
Section: Discussionmentioning
confidence: 99%